Algorithmgraphy as a milestone and phenomenon in the production of still images in the digital era: Resignification of the notion of the photographic image and projection of the medium in a context of image production with artificial intelligence and machine learning - Gómez Gómez, Hernando; Rubio Tamayo, José Luis (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Still images and their production models have evolved significantly in recent years. With today's technology, images can be produced by artificial intelligences (AIs) and with techniques such as algorithm creation and machine learning. This article attempts to investigate the understanding of this phenomenon, analysing the role of the image today and its methods of capture and representation for different purposes (graphics) and trying to contribute to establish a model that would lead us to the concept of algorithmography as a milestone in the production of images.